Comparison the Effect of Echium amoenum Extract with Fluoxetine on Depression in Menopausal Women. A Double-blind Randomized Controlled Trial - Baghbadoranee, Parisa Yousefee (Asian Journal of Pharmaceutics (AJP), 2019)
Introduction: Depression is one of the most commonly reported complaints among menopausal women. Herbal medicines appear to be one of the safe and inexpensive treatments for women suffering from the symptom. Therefore, the present study aimed to compare the impact of Echium amoenum extract with fluoxetine on depression in menopausal women. Methods: This double-blind randomized clinical trial was performed on 72 menopausal women referred to Health Center No. 7 in Ahvaz, Iran. Participants were randomly assigned in two intervention (n = 36) and control groups (n = 36). E. amoenum extract capsule and fluoxetine capsule were packed in similar envelopes with a code number, and then, the participants of both groups received 60 capsules for 8 weeks. The Hamilton depression rating scale (HAM-D) was used to diagnose and analyze the severity of depression. The severity of depression was assessed before intervention and in the 4th, 6th, and 8th weeks after the intervention. Data analysis was performed using SPSS version 21 software through independent t-test, Chi-square, and repeated measures tests. P-value was set less than the significance level (0.05). Findings: At the beginning of the study, the comparison of mean depression scores in both intervention (19 ± 0.477) and control (18.90± 0.440) groups did not show a significant difference (P = 0.889). However, a statistically significant difference was observed in the mean score of depression in both groups in the 4th week of intervention (P ≤ 0.01). No statistically significant difference was found between the mean score of depression in both groups at the end of the study (P = 0.1). Mean scores of depression in participants receiving E. amoenum extract before the intervention also significantly decreased after intervention (P < 0.001). Conclusion: According to the results, hydroalcoholic extract of E. amoenum can improve the symptoms of depression in menopausal women, without any side effects.